1973
DOI: 10.1128/jb.113.2.914-921.1973
|View full text |Cite
|
Sign up to set email alerts
|

The 503-nm Pigment of Escherichia coli B: Characterization and Nutritional Conditions Affecting Its Accumulation

Abstract: Escherichia coli B was shown to contain a pigment with a single symmetrical absorption band at 503 nm, which cannot be attributed to a cytochrome. The absorption of tetrahydroporphyrin in vitro closely resembled that of P-503 in intact cells. The compounds which rendered P-503 colorless, such as cyanide, azide, hydrazine, thiocyanate, hydroxylamine, dithionite, sulfite, and methylcyanide, also rendered tetrahydroporphyrin colorless. The pigment was present when the cells were grown aerobically or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1973
1973
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The 503-nm Pigment Under certain growth conditions, a pigment absorbing at about 503 nm can be observed in reduced-minus-oxidized spectra of E. coli cells. Such conditions include growth aerobically in minimal media with glucose, lactate, or succinate as carbon source or anaerobically with glucose (356) and under iron-limited conditions (Hubbard et al, unpublished data). The absence of this pigment in complex media may be due to its repression by amino acids (348, 356).…”
Section: Ingledew and Poolementioning
confidence: 99%
See 1 more Smart Citation
“…The 503-nm Pigment Under certain growth conditions, a pigment absorbing at about 503 nm can be observed in reduced-minus-oxidized spectra of E. coli cells. Such conditions include growth aerobically in minimal media with glucose, lactate, or succinate as carbon source or anaerobically with glucose (356) and under iron-limited conditions (Hubbard et al, unpublished data). The absence of this pigment in complex media may be due to its repression by amino acids (348, 356).…”
Section: Ingledew and Poolementioning
confidence: 99%
“…ATP is required for association of heme with apocytochrome o. 415 pigment is bleached by cyanide, azide, hydrazine, and dithionite and does not react with CO (356). These authors suggested that the compound was coprotetrahydroporphyrin and, although in kinetic equilibrium with flavoprotein, did not participate in the major electron flux of the respiratory chain.…”
Section: Eb53mentioning
confidence: 99%
“…A pigment absorbing at 503 nm has been detected in different spectra of yeast and several bacteria (74,99). This pigment is not a hemoprotein; it displays the same properties as tetrahydroporphyrin (95,124). Kropinski et al (93) detected this pigment in Zymomonas ATCC 10988; judging from their data, there is not very much present.…”
Section: Ncib 8227mentioning
confidence: 99%
“…The eventual role of this pigment in the metabolism of Zymomonas is not clear. In E. coli this pigment may have some function in electron transport, because it is in kinetic equilibrium with flavoprotein (124).…”
Section: Ncib 8227mentioning
confidence: 99%
“…Determination of cytochrome content. The cytochrome content of cells was estimated by difference spectrophotometry (29). Dithionite-reduced versus oxidized difference spectra were employed to detect and quantitate cytochromes d, b1, and a,.…”
Section: Downloaded Frommentioning
confidence: 99%